Forecasting Inflation in Indonesia Using ARIMAX : The Role of Money Supply and Exchange Rate - Novianda, Besti (Universitas Bangka Belitung, 2025)
Inflation is an essential economic indicator since it signals rising prices for goods and services. Economic factors influence Indonesia's inflation rate, including the money supply and exchange rate. These factors can have an impact not only on inflation at a single point in time but also throughout time. The money supply and exchange rate are two economic factors that substantially influence inflation. As a result, it is critical to forecast Indonesia's inflation rate using money supply and exchange rate as input variables. This study examines the effect of the money supply and exchange rate on the inflation rate. The data used is monthly from 2021-2023 sourced from Bank Indonesia (SEKI BI). This study used the Autoregressive Integrated Moving Average with Exogenous Factor (ARIMAX) technique. The results reveal that the ARIMAX (0,2,1) accurately predicts inflation, as seen by MAPE values of 9.48%. The results also show that the money supply and exchange rate significantly affect the inflation rate in Indonesia. This is due to the impact of the COVID-19 pandemic on Indonesia, which has caused the inverse effect of the exogenous variables. The ARIMAX model can be a valuable and efficient tool for improving forecasting.